Four Wheel Omni Trajectory with Gyrodometry Method in the Indonesia 2022 Ash Robot Contest - Imam Sutrisno; Daffa Alifian Harlinanda; Zindhu Maulana Ahmad; Projek Priyonggo; Aprinaldi Jasa Mantau; Ari Wibawa Budi Santosa; Muhammad Khalil; Fahmi Umasangadji (Indonesian Journal of Innovation Multidisipliner Research, 2024)
The National Achievement Center (Puspresnas) and the Ministry of Education and Culture of the Republic of Indonesia proudly present the Indonesian Ash Robot Contest (KRAI), a yearly student robotics competition where teams tackle ash-related challenges with their robot creations. At KRAI 2021, it was shown that many robots were controlled using joysticks and resulted in a lack of effectiveness in robotic motion. The use of a joystick makes the movement of the robot take longer. This is because the robot is controlled by humans and the robot has not been able to pinpoint the robot's location. Gyrodometry is a method to map the robot's position using a inner ear and compass of the machine. In this research, Gyrodometry is used to map the position based on the readings of the gyroscope sensor and rotary encoder so that the robot can move automatically. In this research, the KRAI hitter robot can map positions and move in an accurate direction and can move automatically and effectively so that it can save more time and can increase the possibility of strategy in the match. From the results of this study, it was found that without using gyrodometry the error of X reached 11.825 cm and Y reached 35.1325 cm and also the angle error reached 13.7 degrees. and by using gyrodometry error X reaches 4.25 cm and Y reaches 5.775 cm and angle error 2.01 degrees. From these results, it was found that using gyrodometry was better than without using gyrodometry. The addition of waypoints to the robot only produces an average error of 8.2 cm X and Y error of -7.8 cm and the angle error reaches 10.2 degrees.